Prognosis Model for Investigating the Evaporation of Water Droplets; Journal of Engineering Physics and Thermophysics; Vol. 92, iss. 4 - Antonov D. V. Dmitry Vladimirovich; Vysokomornaya O. V. Olga Valeryevna; Kuznetsov G. V. Geny Vladimirovich; Piskunov M. V. Maksim Vladimirovich (2019, 2019)
Title screen